Mesochaetopterus sagittarius: an example of a biogeography discrepancy between larval and adult boundaries: implication for recruitment studies - Bhaud, MR (2012)
A geographic discrepancy between the distribution boundaries for larvae and adults of the chactopterid Mesochaetopterus sagittarius was recorded. The most northerly position where benthic individuals, probably not reproductive, have been collected in the Atlantic corresponds to the latitude of Aveiro (Portugal). The most northerly position for larvae corresponds to that of Arcachon (France). The larvae found off Arcachon constitute an influx of subtropical origin. They rarely succeed in passing the fixation stage, and when they do, the benthic stage is not capable of reproduction. The occupation of a very large zone by planktonic larvae spread over 4degrees of latitude (500 km), eventually resulting in sterile benthic populations, confirms that environmental constraints are less severe on larvae than on adults. This work emphasizes,, through the integration of different oceanographic disciplines, the importance of knowing the structure of the spatial distribution of adults when seeking to achieve a better understanding of local recruitment.